2023
DOI: 10.3390/life13061303
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin, a Natural Compound with Several Biological Effects and Anti-Inflammatory Properties

Abstract: Phytochemicals from various medicinal plants are well known for their antioxidant properties and anti-cancer effects. Many of these bioactive compounds or natural products have demonstrated effects against inflammation, while some showed a role that is only approximately described as anti-inflammatory. In particular, naphthoquinones are naturally-occurring compounds with different pharmacological activities and allow easy scaffold modification for drug design approaches. Among this class of compounds, Plumbagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 90 publications
(188 reference statements)
0
9
0
Order By: Relevance
“…7,15 Shikonin, a naphthoquinone found in the roots of Lithospermum erythrorhizon Siebold & Zucc, 16 has attracted attention for its therapeutic properties. 14 However, the overexploitation of shikonin-producing plants has raised environmental concerns. 15 In contrast, 3,5,8-trihydroxy-6-methoxy-2-(5oxohexa-1,3-dienyl)-naphthanthene-1,4-dione (3,5,8-TMON, 2) is a naturally occurring naphthoquinone produced by the fungus Cordyceps sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,15 Shikonin, a naphthoquinone found in the roots of Lithospermum erythrorhizon Siebold & Zucc, 16 has attracted attention for its therapeutic properties. 14 However, the overexploitation of shikonin-producing plants has raised environmental concerns. 15 In contrast, 3,5,8-trihydroxy-6-methoxy-2-(5oxohexa-1,3-dienyl)-naphthanthene-1,4-dione (3,5,8-TMON, 2) is a naturally occurring naphthoquinone produced by the fungus Cordyceps sp.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several naphthoquinones have been investigated for their biological activities, encompassing antimalarial, 9 anti-cancer, 10,11 antimycobacterial, 12,13 and anti-inflammatory properties. 14 Notable examples of plant-derived naphthoquinones used in biological activity assessments include lawsone, lapachol, β-lapachone, plumbagin, and shikonin (see Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its antibacterial and anti‐inflammatory activities, the plant has been used medically in Eastern cultures to treat rheumatoid arthritis, parasite infections, dermatological problems, and infectious diseases 14 . Plumbagin's primary mechanism of action in cancer cells is the activation of apoptosis through the increased production of ROS and cell cycle arrest by the induction of DNA strand breaks 14–16 . Additionally, inhibition of electron transport and uncoupling of oxidative phosphorylation (OxPhos), and the intercalation in the DNA structure or a bioreductive alkylation of biomolecules have been reported 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…14 Plumbagin's primary mechanism of action in cancer cells is the activation of apoptosis through the increased production of ROS and cell cycle arrest by the induction of DNA strand breaks. [14][15][16] Additionally, inhibition of electron transport and uncoupling of oxidative phosphorylation (OxPhos), and the intercalation in the DNA structure or a bioreductive alkylation of biomolecules have been reported. 17,18 Recent cancer research has focused on plumbagin, and promising findings have been reported in cases of several cancer types, including lung, prostate, breast, cervical, colorectal cancer, leukemia, and melanoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation